Bahasa Inggris - Waspodo, Lego (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2021)
The purpose of this research was to determine the variables that influence whistleblowing in Java, Indonesia. The elements referred to were those associated with Javanese culture, namely tepo seliro and retribution. The data collecting process included the distribution of questionnaires to 35 workers of the Public Accountant Offices in Java, and the study sample consisted of Javanese accountants. The data collecting method utilized was purposive sampling with criteria established in accordance with the study goals. Meanwhile, SPSS was utilized for data analysis. The findings supported the tested hypothesis that Javanese culture has an effect on whistleblowing activities and that retribution has an effect on whistleblowing acts.